Ultrathin copper foil with carrier and method for producing the same
By forming an organic copper composite release layer containing copper nitrogen bonds on the support copper foil, the problem of uneven thickness and content of the release layer in the prior art is solved, and better release performance and controllability are achieved.
Patent Information
- Application Number
- JP2023218696
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-01
- Filing Date
- 2023-12-25
- Publication Date
- 2025-05-15
AI Technical Summary
After hot pressing of existing ultra-thin copper foil products, the thickness and content of the release layer are uneven, making it difficult to control the peeling force.
An organic copper composite containing a copper nitrogen bond (Cu-N bond) is used as the release layer material, and a release layer is formed on the support copper foil by electroplating, and the composition and thickness of the release layer are controlled in a specific electroplating solution.
The good release performance between the carrier copper foil and the ultra-thin copper foil is achieved, the problem of difficult to control the peeling force is solved, and the thickness and content of the release layer are more uniform.
Smart Images

Figure 2025076229000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper foil, and more particularly to an ultra-thin copper foil with a carrier and a method for producing the same. [Background technology]
[0002] In the prior art, the manufacture of fine pitch printed circuit boards (PCBs) is carried out by the production of ultra-thin copper foil, which is a laminated structure of an ultra-thin copper layer, a release layer, and a carrier copper foil.
[0003] In conventional ultra-thin copper foil products, after prepreg (semi-cured laminate sheet) and hot pressing, the distribution and magnitude of the peel force between the ultra-thin copper foil and the carrier copper foil are related to the distribution and content of the release layer.
[0004] The release layer in conventional ultra-thin copper foil products is made of single or multiple alloy metals. The metal components include Ni, Co, Mo, W, or a combination thereof. However, the release layer deposited on the carrier copper foil by electrolytic plating has a non-uniform thickness and content, which makes it difficult to control the peel force.
[0005] Therefore, in view of the fact that the above-mentioned problems can be improved, the inventors conducted intensive research and applied scientific theory, and as a result, arrived at the present invention as a method that is rational in design and can effectively improve the above-mentioned problems. Summary of the Invention [Problem to be solved by the invention]
[0006] The technical problem to be solved by the present invention is to provide an ultra-thin copper foil with a carrier and a manufacturing method thereof in response to the shortcomings of the conventional technology. [Means for solving the problem]
[0007] In order to solve the above technical problems, one technical means adopted by the present invention provides a method for manufacturing an ultra-thin copper foil with a carrier. The method for manufacturing an ultra-thin copper foil with a carrier includes providing a carrier copper foil, forming a release layer containing a copper-containing organic compound on one side of the carrier copper foil, the chemical structure of the copper-containing organic compound having at least a copper-nitrogen bond (Cu-N bond), and forming an ultra-thin copper layer (ultra-thin copper foil) on the side of the release layer away from the carrier copper foil, and the carrier copper foil can be peeled off from the ultra-thin copper layer via the release layer.
[0008] Preferably, the release layer has a Fourier transform infrared spectroscopy (FTIR) spectrum of 1020 cm -1 ~1025cm -1 And, 1098cm -1 ~1103cm -1 The infrared characteristic absorption peaks are shown at each of the positions.
[0009] Preferably, the copper-containing organic compound for forming the release layer is an organic copper complex.
[0010] Preferably, the release layer is formed on the carrier copper foil by electrolytic plating using an electrolytic plating solution, the electrolytic plating solution containing (1) a nitrogen-containing heterocyclic compound, (2) a copper-containing metal salt, and (3) a buffer, the concentration of the nitrogen-containing heterocyclic compound in the electrolytic plating solution being 0.05 g / L to 40 g / L, the concentration of the copper-containing metal salt being 5 g / L to 100 g / L, and the concentration of the buffer being 10 g / L to 600 g / L.
[0011] Preferably, in the electrolytic plating solution, the ratio (by mass) of the nitrogen-containing heterocyclic compound:the copper-containing metal salt:the buffer is 1:5-40:100-600.
[0012] Preferably, the nitrogen-containing heterocyclic compound is a bicyclic nitrogen-containing heterocyclic compound, the copper-containing metal salt is at least one selected from the group consisting of copper pyrophosphate, copper sulfate, copper carbonate, copper acetate, copper nitrate, copper oxide, copper(I) cyanide, sodium copper cyanide, and potassium copper cyanide, and the buffer is at least one selected from the group consisting of potassium pyrophosphate, boric acid, sulfuric acid, ammonium sulfate, citric acid, ammonium citrate, sodium citrate, sodium acetate, sodium carbonate, potassium tartrate, and sodium gluconate.
[0013] Preferably, the carrier copper foil is electrolytically plated in the electrolytic plating solution for a predetermined time, the predetermined time being 1 to 20 seconds, and the electrolytic plating conditions include a current density of 0.1 to 5 ASD (A / dm 2 ) and the temperature of the electrolytic plating solution is 30 to 60°C.
[0014] Preferably, the chemical structure of the copper-containing organic compound further includes a carbon-hydrogen bond (CH bond), a carbon-nitrogen bond (CN bond), and a nitrogen-hydrogen bond (NH bond).
[0015] Preferably, the release layer has a nitrogen content of 0.1 to 25% by mass as measured by an X-ray photoelectron spectroscopy (XPS).
[0016] Preferably, the elemental ratios of the release layer analyzed by the X-ray photoelectron spectrometer are an N1s peak area of 15 to 25 atomic%, an O1s peak area of 25 to 35 atomic%, a C1s peak area of 30 to 40 atomic%, and a Cu2p peak area of 5 to 18 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.3 to 0.9.
[0017] In order to solve the above technical problems, another technical means adopted by the present invention provides an ultra-thin copper foil with a carrier. The ultra-thin copper foil with a carrier includes a carrier copper foil, a release layer formed on one side of the carrier copper foil, and an ultra-thin copper layer (ultra-thin copper foil) formed on the side of the release layer away from the carrier copper foil, the release layer includes a copper-containing organic compound, the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu-N bond), and the carrier copper foil can be peeled off from the ultra-thin copper layer via the release layer.
[0018] Preferably, the release layer has a Fourier transform infrared spectroscopy (FTIR) spectrum of 1020 cm -1 ~1025cm -1 Position and 1098cm -1 ~1103cm -1 and the copper-containing organic compound of the release layer is an organic copper complex.
[0019] Preferably, the carrier copper foil has a thickness of 10 μm to 50 μm, the release layer has a thickness of 20 nm to 300 nm, and the ultra-thin copper layer has a thickness of 1 μm to 5 μm.
[0020] Preferably, the release layer is formed on the carrier copper foil by electrolytic plating using an electrolytic plating solution, and the electrolytic plating solution contains (1) a nitrogen-containing heterocyclic compound, (2) a copper-containing metal salt, and (3) a buffer.
[0021] Preferably, the surface roughness of the ultra-thin copper layer on a surface away from the release layer is greater than the surface roughness of the ultra-thin copper layer on a surface in contact with the release layer.
[0022] Preferably, the peel strength when the carrier copper foil is peeled from the ultrathin copper layer via the release layer is 1 to 20 gf / cm based on JIS Z 0237-2009.
[0023] Preferably, the release layer exhibits characteristic absorption peaks of carbon-hydrogen bonds (CH bonds), carbon-nitrogen bonds (CN bonds), and nitrogen-hydrogen bonds (NH bonds) by Fourier transform infrared spectroscopy (FTIR).
[0024] Preferably, the nitrogen content of the release layer measured by an X-ray photoelectron spectroscopy (XPS) is 0.1 mass% to 25 mass%, and the elemental ratios of the release layer analyzed by the X-ray photoelectron spectroscopy are an N1s peak area of 15 to 25 atomic%, an O1s peak area of 25 to 35 atomic%, a C1s peak area of 30 to 40 atomic%, and a Cu2p peak area of 5 to 18 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.3 to 0.9.
[0025] Preferably, the N1s peak area accounts for 20.63 atomic%, the O1s peak area accounts for 29.78 atomic%, the C1s peak area accounts for 36.77 atomic%, the Cu2p peak area accounts for 12.82 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.6214.
[0026] Preferably, in X-ray photoelectron spectroscopy (XPS) and focused ion beam analysis (FIB) of the release layer, a curve diagram of a Cu2p peak is present. Effect of the Invention
[0027] As an advantageous effect of the present invention, the ultra-thin copper foil with a carrier and its manufacturing method according to the present invention has a technical feature that "the ultra-thin copper foil with a carrier comprises a carrier copper foil, a release layer formed on one side of the carrier copper foil, and an ultra-thin copper layer (ultra-thin copper foil) formed on the side of the release layer away from the carrier copper foil, the release layer contains a copper-containing organic compound, and the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu-N bond)". Due to this technical feature, the carrier copper foil and the ultra-thin copper layer in the ultra-thin copper foil with a carrier have excellent releasability, and this solves the problem that in the conventional technology, the release layer is not uniform in thickness and content, making it difficult to control the peel force. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a schematic diagram of step S110 of the method for producing an ultrathin copper foil with a carrier according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of step S120 of the method for producing an ultra-thin copper foil with a carrier according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram of step S130 of the method for producing an ultra-thin copper foil with a carrier according to an embodiment of the present invention. [Figure 4] 1 is a schematic diagram of step S210 of the method for manufacturing a printed circuit board according to an embodiment of the present invention. [Diagram 5] 1 is a schematic diagram of step S220 of the method for manufacturing a printed circuit board according to an embodiment of the present invention. [Figure 6] 1 is a schematic diagram of step S230 of the method for manufacturing a printed circuit board according to an embodiment of the present invention. [Figure 7] FIG. 2 is a schematic diagram showing the formation of an ultra-thin copper foil layer on a dielectric layer material according to an embodiment of the present invention. [Figure 8] FIG. 2 is a schematic diagram showing how a carrier copper foil according to an embodiment of the present invention is immersed in an electrolytic plating solution to perform electrolytic plating. [Figure 9] FIG. 1 is a schematic diagram showing that the carrier copper foil of an embodiment of the present invention is a continuous rollable sheet. [Figure 10]1 is a schematic diagram showing the effect of a release layer formed with different organic compound concentrations in an electrolytic plating solution on the peel strength between a carrier copper foil and an ultrathin copper layer. [Figure 11] FIG. 2 is a diagram showing a characteristic absorption peak spectrum obtained by Fourier transform infrared spectroscopy (FTIR) of the release layer of the ultra-thin copper foil with a carrier according to an embodiment of the present invention. [Figure 12] FIG. 2 is a curve diagram showing a Cu2p peak in an X-ray photoelectron spectroscopy (XPS) and a focused ion beam analysis (FIB). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] In order to better understand the features and technical contents of the present invention, please refer to the following detailed description of the present invention and the accompanying drawings, which are provided for reference and explanation only and are not intended to limit the scope of the present invention.
[0030] Hereinafter, the embodiments of the present invention will be described with reference to certain specific embodiments, so that those skilled in the art can understand the advantages and effects of the present invention based on the contents disclosed in this specification.
[0031] In addition, as described above, the accompanying drawings of the present invention are simple schematic illustrations and are not drawn based on actual size. The present invention can be implemented or applied by other different specific embodiments, and each detail in the specification can be modified and changed in various ways based on different perspectives and applications without departing from the concept of the present invention. The technical contents of the present invention will be described in more detail based on the following embodiments, but the disclosed contents do not limit the protection scope of the present invention.
[0032] It should be understood that, although the present specification may use the terms "first", "second", "third" and the like to describe various elements or signals, these elements or signals are not limited by these terms. These terms are mainly used to distinguish one element from another element or one signal from another signal. In addition, the term "or" used in the present specification may include any one or more combinations of the associated listed items according to actual circumstances.
[0033] [Manufacturing method of ultra-thin copper foil with carrier] As shown in Figures 1 to 3, in an embodiment of the present invention, a method for producing an ultra-thin copper foil with a carrier is provided, which includes steps S110, S120, and S130. It should be noted that the order and operation method of each step in this embodiment can be adjusted according to needs and is not limited thereto. It should be noted that the copper foil material formed by the method for producing an ultra-thin copper foil with a carrier in this embodiment is suitable for manufacturing a substrate for a printed circuit board, but the present invention is not limited thereto.
[0034] As shown in Fig. 1, the step S110 includes providing a carrier copper foil 1. Here, the carrier copper foil 1 may be, for example, an electrolytic copper foil or a rolled copper foil. In one embodiment of the present invention, the carrier copper foil 1 is an electrolytic copper foil, but the present invention is not limited thereto.
[0035] Regarding the thickness, the carrier copper foil 1 has a thickness of, for example, 10 μm to 50 μm, preferably 15 μm to 40 μm, and particularly preferably 18 μm to 35 μm.
[0036] In this embodiment, the step S110 includes washing the carrier copper foil 1 with water to remove impurities or chemical residues on the surface of the carrier copper foil 1, but the present invention is not limited thereto.
[0037] As shown in FIG. 2, the step S120 includes forming a release layer 2 on one side of the carrier copper foil 1. The release layer 2 includes a copper-containing organic compound (also called a copper-based polymer), and the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu-N bond). In one embodiment, the release layer 2 includes 80 wt % or more of the copper-containing organic compound, and is preferably made of the copper-containing organic compound. It is worth noting that the copper-nitrogen bond (Cu-N bond) in the structure of the copper-containing organic compound can be measured, for example, by Fourier-transform infrared spectroscopy (FTIR).
[0038] For example, as shown in FIG. 11, the release layer 2 containing a copper-containing organic compound has a surface area of 10 -1 ~1025cm -1 Position and 1098cm -1 ~1103cm -1 This indicates that the chemical structure of the copper-containing organic compound contains at least a copper-nitrogen bond.
[0039] In one embodiment of the present invention, the copper-containing organic compound is an organic copper complex, but the present invention is not limited thereto.
[0040] Regarding the thickness, the release layer 2 has a thickness of, for example, 20 nm to 300 nm, preferably 35 nm to 200 nm, and particularly preferably 50 nm to 100 nm.
[0041] More specifically, as shown in FIGS. 8 and 9, the release layer is formed on the carrier copper foil 1 by electroplating using an electroplating solution L (electroplating solution).
[0042] That is, the release layer 2 is formed by performing electrolysis using the electrolytic plating solution L. In this embodiment, the electrolytic plating solution contains the following components (1) to (3). (1) Nitrogen-containing heterocyclic compound (2) Copper-containing metal salts (3) Buffer
[0043] Here, (1) the nitrogen-containing heterocyclic compound is an organic compound, and is preferably a bicyclic nitrogen-containing heterocyclic compound, and more preferably benzotriazole, but the present invention is not limited thereto. For example, the bicyclic nitrogen-containing heterocyclic compound may be indoline or 1,4-diazabicyclo[2.2.2]octane, etc.
[0044] Here, the chemical formula of benzotriazole is C6H5N3 and its chemical structure is as follows: [ka]
[0045] The concentration of the nitrogen-containing heterocyclic compound in the electrolytic plating solution L is 0.05 g / L to 40 g / L, preferably 0.1 g / L to 20 g / L, and particularly preferably 0.1 g / L to 10 g / L.
[0046] It is worth noting that the nitrogen-containing heterocyclic compound is a supply source of the organic substance in the copper-containing organic compound for forming the release layer 2 .
[0047] More specifically, (2) the copper-containing metal salt belongs to an inorganic compound. The copper-containing metal salt is a source of copper element in the release layer 2 (or a source of copper ions in the electrolytic plating solution L). The copper-containing metal salt and (1) the nitrogen-containing heterocyclic compound are formed as an organic copper complex, and the release layer 2 can be formed on the carrier copper foil 1.
[0048] In one embodiment of the present invention, the copper-containing metal salt may be at least one selected from the group consisting of copper pyrophosphate, copper sulfate, copper carbonate, copper acetate, copper nitrate, copper oxide, cuprous cyanide, sodium copper cyanide, and potassium copper cyanide. In one preferred embodiment of the present invention, the copper-containing metal salt is copper pyrophosphate, whose chemical formula is Cu2P2O7 and whose chemical structure is as follows:
[0049] The following chemical structure shows the dissociated state of copper pyrophosphate in water. [ka]
[0050] The concentration of the copper-containing metal salt (for example, copper pyrophosphate) in the electrolytic plating solution L is 5 g / L to 100 g / L, preferably 5 g / L to 50 g / L, and particularly preferably 10 g / L to 30 g / L.
[0051] To further explain, (3) the buffer can better disperse or dissolve the copper-containing metal salt in the electroplating solution L and can be used to adjust the pH value of the electroplating solution L, but the present invention is not limited thereto.
[0052] In one embodiment of the invention, the buffer may be at least one selected from the group consisting of potassium pyrophosphate, boric acid, sulfuric acid, ammonium sulfate, citric acid, ammonium citrate, sodium citrate, sodium acetate, sodium carbonate, potassium tartrate, and sodium gluconate.
[0053] In one preferred embodiment, the buffer is potassium pyrophosphate, whose chemical formula is K4P2O7 and whose chemical structure is as follows:
[0054] The following chemical structure shows the dissociated state of potassium pyrophosphate in water. [ka]
[0055] The concentration of the buffer (for example, potassium pyrophosphate) in the electrolytic plating solution L is 10 g / L to 600 g / L, preferably 100 g / L to 500 g / L, and particularly preferably 200 g / L to 500 g / L.
[0056] In one embodiment of the present invention, the mass ratio of all organic compounds (e.g., nitrogen-containing heterocyclic compounds):copper-containing metal salt (e.g., copper pyrophosphate):buffer (e.g., potassium pyrophosphate) in the electrolytic plating solution L is, for example, 1:5-40:100-600, preferably 1:10-30:100-500, and particularly preferably 1:15-25:200-500, but the present invention is not limited thereto. However, the present invention is not limited to the concentration ranges described in the above embodiment.
[0057] In this embodiment, the liquid component of the antioxidant liquid 2 is water, which may be, for example, deionized water (DI), reverse osmosis water (RO), or ultrapure water (MQ), but the present invention is not limited thereto.
[0058] 8, the electrolytic plating method in this embodiment is to form a release layer 2 on at least one surface of the carrier copper foil 1 by immersing the carrier copper foil 1 in an electrolytic plating solution L and performing electrolytic plating. Here, the electrolytic plating solution L can be placed in advance in a storage tank T, for example.
[0059] More specifically, the carrier copper foil 1 is electrolyzed in the electrolytic plating solution 2 for a predetermined time, so that the release layer 2 is formed on at least one surface of the carrier copper foil 1 .
[0060] In one embodiment of the present invention, the predetermined time is 1 to 20 seconds, preferably 1 to 15 seconds, and particularly preferably 3 to 15 seconds. For example, the predetermined time may be 3, 5, 7, 9, 11, 13, or 15 seconds.
[0061] The electrolytic plating conditions for the carrier copper foil 1 in the electrolytic plating solution L are a current density of 0.1 ASD to 5 ASD (i.e., A / dm 2 , amperes per square centimeter). For example, the current density may be 0.2 ASD, 0.6 ASD, 1.0 ASD, 1.5 ASD, or 2 ASD.
[0062] More specifically, the liquid temperature of the electrolytic plating solution L is 30° C. to 60° C., and preferably 40° C. to 60° C. For example, the liquid temperature of the electrolytic plating solution L may be 40° C., 45° C., 50° C., 55° C., or 60° C.
[0063] It should be noted that, in this embodiment, the carrier copper foil 1 is described as being a sheet of copper foil immersed in the electrolytic plating solution L, but the present invention is not limited thereto.
[0064] 9, in another embodiment of the present invention, the carrier copper foil 1 is a bendable continuous sheet. The carrier copper foil 1 is placed inside a storage tank T and guided into the electrolytic plating solution L by a number of guide rollers R around the carrier copper foil 1.
[0065] The carrier copper foil 1 can be electrolyzed for a predetermined time while staying in the electrolytic plating solution L by controlling the scroll speed of a plurality of guide rollers R.
[0066] More specifically, at least a pair of electrodes E are further installed in the storage tank T, and by energizing the electrodes E, electrolytic plating of the carrier copper foil 1 immersed in the electrolytic plating solution L can be performed, thereby forming the release layer. However, the present invention is not limited to this.
[0067] The step S120 further includes removing the carrier copper foil 1 on which the release layer 2 is formed, and removing excess liquid components (for example, moisture) from the release layer 2 by blowing air and drying.
[0068] With the above-mentioned configuration, the release layer 2 can be formed on the carrier copper foil 1 by electroplating using an electroplating solution L. That is, the release layer 2 is formed by the electroplating solution L.
[0069] As shown in FIG. 3, the step S130 includes forming an ultra-thin copper layer 3 on the surface of the release layer 2 remote from the carrier copper foil 1.
[0070] In one embodiment of the present invention, the ultra-thin copper layer 3 may be formed by depositing copper metal on the release layer 2 by, for example, a wet electrolytic / electroplating process, but the present invention is not limited thereto.
[0071] Regarding the thickness, the ultrathin copper layer 3 has a thickness of, for example, 1 μm to 5 μm, preferably 1.5 μm to 4 μm, and particularly preferably 1.5 μm to 3 μm.
[0072] It is noteworthy that the surface of the ultra-thin copper layer 3 away from the release layer 2 is a rough surface with irregularities, as shown in Fig. 3. That is, the surface roughness (e.g., Ra) of the surface of the ultra-thin copper layer 3 away from the release layer 2 is greater than the surface roughness of the surface of the thin copper layer 3 in contact with the release layer 2, but the present invention is not limited thereto.
[0073] With the above-mentioned configuration, the laminate composed of the carrier copper foil 1, the release layer 2, and the ultra-thin copper layer 3 is defined as the ultra-thin copper foil E with carrier (also referred to as copper foil laminate structure E) according to an embodiment of the present invention.
[0074] In one embodiment of the present invention, the carrier copper foil 1 can be peeled off from the ultrathin copper layer 3 via the release layer 2. The peel strength when the carrier copper foil 1 is peeled off from the ultrathin copper layer 3 via the release layer 2 is, for example, 1 to 20 gf / cm, and preferably 5 to 10 gf / cm.
[0075] Here, the peel strength is a value measured based on JIS Z 0237-2009, but the present invention is not limited thereto.
[0076] With the above-mentioned configuration, the carrier copper foil 1 has excellent releasability between the carrier copper foil 1 and the ultra-thin copper layer 3 due to the design of the specific release layer 2, thereby solving the problem in the conventional technology that it is difficult to control the peel force due to the non-uniform thickness and content of the release layer.
[0077] It is noteworthy that in the above embodiment, the laminate composed of the carrier copper foil 1, the release layer 2, and the ultra-thin copper layer 3 was subjected to heat treatment at 180 to 220°C for 70 to 110 minutes, and then the peel strength was measured to obtain the above measurement results.
[0078] To explain further, FIG. 10 shows the effect of a release layer formed with different concentrations of organic compounds (which may be abbreviated as organic concentration, in units of g / L) in the electrolytic plating solution on the peel force (peel strength) between the carrier copper foil and the ultrathin copper layer.
[0079] Here, in one specific example of the present invention (for example, Example 1 in FIG. 10), the concentration of the organic chemical in the electrolytic plating solution L for forming the release layer was 1 g / L (including benzotriazole), the concentration of copper pyrophosphate (a source of copper ions) was 20 g / L, and the concentration of potassium pyrophosphate was 390 g / L. Here, the current density of the electrolytic plating was 0.2 to 2 ASD (for example, 1 ASD), the plating time was 3 to 15 seconds (for example, 9 seconds), and the plating temperature was 40 to 60°C (for example, 50°C), to obtain an ultra-thin copper foil E with a carrier. The obtained ultra-thin copper foil E with a carrier and a dielectric layer material PP (for example, prepreg) were heat-treated at 200°C for 90 minutes, and then a hardboard material was obtained. The peel strength between the carrier copper foil and the ultra-thin copper layer in the hardboard material was about 5 gf / cm.
[0080] In other experimental sets, the concentration ratio of the organic compound (g / L) to the copper pyrophosphate (copper ion source) was fixed, for example, in Example 2, the organic compound was combined with 0.95 g / L of the copper pyrophosphate (copper ion source) at 19 g / L, that is, the weight ratio of the organic compound to the copper pyrophosphate (copper ion source) was 1:20. According to the experimental table in FIG. 10, by controlling the concentration of the organic compound in the electrolytic plating solution L, the peel strength between the carrier copper foil and the ultrathin copper layer can be controlled within a desired range to achieve excellent peeling force.
[0081] It is worth noting that, as described above, according to the measurement results of Example 1, the release layer 2 contains a copper-containing organic compound, and its chemical structure has at least a copper-nitrogen bond (Cu-N bond). Also, as shown in Fig. 11, according to Fourier transform infrared spectroscopy (FTIR), the release layer has characteristic absorption peaks of a carbon-hydrogen bond (CH bond, CH bond), a carbon-nitrogen bond (CN bond, CN bond), and a nitrogen-hydrogen bond (NH bond, NH bond).
[0082] More specifically, the nitrogen content of the release layer 2 measured by X-ray photoelectron spectroscopy (XPS) is 0.1 to 25% by mass, and preferably 1 to 20% by mass. For example, the nitrogen content of the release layer 2 may be 5%, 10%, 15%, or 20% by mass.
[0083] From another point of view, the element ratios (atomic%) of the release layer analyzed by the X-ray photoelectron spectrometer (XPS) are as follows: N1s peak area (related to nitrogen element) is 15 to 25 atomic%, O1s peak area (related to oxygen element) is 25 to 35 atomic%, C1s peak area (related to carbon element) is 30 to 40 atomic%, and Cu2p peak area (related to copper element) is 5 to 18 atomic%. More specifically, the value of the ratio of the Cu2p peak area to the N1s peak area is 0.3 to 0.9, and preferably 0.5 to 0.7, but the present invention is not limited thereto.
[0084] In one specific example of the present invention, the elemental ratios of the release layer 2 analyzed by the X-ray photoelectron spectroscopy (XPS) are as follows: N1s peak area is 20.63 atomic%, O1s peak area is 29.78 atomic%, C1s peak area is 36.77 atomic%, and Cu2p peak area is 12.82 atomic%.
[0085] The table below shows the element ratios (atomic %) obtained by XPS analysis.
[0086] [Table 1]
[0087] The ratio of the Cu2p peak area to the N1s peak area is 0.6214 (that is, 12.82 divided by 20.63).
[0088] 12 shows curves indicating a Cu2p peak in X-ray photoelectron spectroscopy (XPS) and focused ion beam analysis (FIB). That is, the release layer 2 of the present invention certainly contains copper element.
[0089] From the above qualitative analysis, it is found that the organocopper complex constituting the release layer 2 certainly contains the above benzotriazole (nitrogen-containing organic compound).
[0090] It should be noted that the nitrogen element in the release layer 2 originates from the nitrogen-containing organic compound contained in the electrolytic plating solution L.
[0091] It is worth noting that X-ray photoelectron spectroscopy (XPS) is a quantitative energy spectroscopy method for measuring the elemental composition, empirical formula, and chemical and electronic states of the elements contained in a material. This technique irradiates the material to be analyzed with X-rays and simultaneously measures the kinetic energy and number of electrons that escape within a range of 1 nm to 10 nm below the surface of the material to obtain an X-ray photoelectron spectrum.
[0092] [Ultra-thin copper foil with carrier] The above is a technical description of the manufacturing method of an ultra-thin copper foil with a carrier according to an embodiment of the present invention. As shown in FIG. 3, an ultra-thin copper foil E with a carrier (also called a copper foil laminate structure) is also provided in the embodiment of the present invention. The ultra-thin copper foil E with a carrier includes a carrier copper foil 1, a release layer 2 formed on the carrier copper foil 1, and an ultra-thin copper layer 3 formed on the surface of the release layer 2 away from the carrier copper foil 1.
[0093] Here, in one embodiment of the present invention, the carrier copper foil 1 is an electrolytic copper foil, and the thickness of the carrier copper foil 1 is 10 μm to 50 μm, preferably 15 μm to 40 μm, and particularly preferably 18 μm to 35 μm, but the present invention is not limited thereto.
[0094] The release layer 2 contains a copper-containing organic compound, and the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu—N bond).
[0095] It is worth noting that the copper-nitrogen bond (Cu-N bond) in the chemical structure of the copper-containing organic compound may be detected, for example, by Fourier transform infrared spectroscopy. For example, as shown in FIG. 11, the release layer 2 containing the copper-containing organic compound has a wavelength of 1020 cm -1 ~1025cm -1 And, 1098cm -1 ~1103cm -1 This indicates that the chemical structure of the copper-containing organic compound contains at least a copper-nitrogen bond. The copper-containing organic compound may be an organic copper complex, but the present invention is not limited thereto.
[0096] The thickness of the release layer 2 is, for example, 20 nm to 300 nm, preferably 35 nm to 200 nm, and particularly preferably 50 nm to 100 nm.
[0097] The release layer 2 is formed on the carrier copper foil 1 by electrolysis using an electrolytic plating solution L. Here, the electrolytic plating solution L contains (1) a nitrogen-containing heterocyclic compound, (2) a copper-containing metal salt (e.g., copper pyrophosphate), and (3) a buffer (e.g., potassium pyrophosphate).
[0098] Here, the characteristics of each component in the electrolytic plating solution have already been described above, so they will not be described here again.
[0099] It is worth noting that the nitrogen-containing heterocyclic compound is a supply source of the organic substance in the copper-containing organic compound for forming the release layer 2 .
[0100] The copper-containing metal salt is a supply source of elemental copper in the release layer 2 .
[0101] More specifically, the ultra-thin copper layer 3 may be formed, for example, by depositing copper metal on the release layer 2 using a wet electrolysis / electroplating process. The thickness of the ultra-thin copper layer 3 is 1 μm to 5 μm, preferably 1.5 μm to 4 μm, and particularly preferably 1.5 μm to 3 μm.
[0102] In this embodiment, the surface of the ultrathin copper layer 3 away from the release layer 2 has an uneven, rough surface, but the present invention is not limited to this.
[0103] Here, the carrier copper foil 1 can be peeled off from the ultrathin copper layer 3 via the release layer 2. The peel strength when the carrier copper foil 1 is peeled off from the ultrathin copper layer 3 via the release layer 2 is, for example, 1 to 20 gf / cm, and preferably 5 to 10 gf / cm. The peel strength is, for example, a value measured based on JIS Z 0237-2009, but the present invention is not limited thereto.
[0104] With the above-mentioned configuration, the carrier copper foil 1 has excellent releasability between the carrier copper foil 1 and the ultra-thin copper layer 3 due to the specific design of the release layer 2.
[0105] [Manufacturing method of printed circuit boards] As shown in FIGS. 4 to 7, the embodiment of the present invention also provides a method for manufacturing a printed circuit board including steps S210, S220, and S230.
[0106] As shown in FIG. 4, the step S210 includes attaching the ultra-thin copper foil 3 with a carrier according to the embodiment to a dielectric layer material PP (for example, a prepreg sheet) via an ultra-thin copper layer 3.
[0107] 5, the process S220 includes performing a hot pressing process H on the ultra-thin copper foil E with carrier and the dielectric layer material PP, so that the concave-convex microstructure on the rough surface of the ultra-thin copper layer 3 can be tightly adhered to the dielectric layer material PP, and the adhesion between the ultra-thin copper layer 3 and the dielectric layer material PP can be improved.
[0108] As shown in Fig. 6, the step S230 includes separating the release layer 2 and the ultra-thin copper layer 3 in the carrier copper foil 1, so that the ultra-thin copper layer 3 remains on the dielectric layer material PP. Fig. 7 is a schematic diagram showing the adhesion of the ultra-thin copper layer 3 to the dielectric layer material PP.
[0109] The above is a method for manufacturing a printed circuit board according to one embodiment of the present invention, but the application of the ultra-thin copper foil E with carrier is not limited to the above method.
[0110] [Advantageous Effects of the Embodiments] As an advantageous effect of the present invention, the ultra-thin copper foil with a carrier and its manufacturing method according to the present invention has a technical feature that "the ultra-thin copper foil with a carrier comprises a carrier copper foil, a release layer formed on one side of the carrier copper foil, and an ultra-thin copper layer (ultra-thin copper foil) formed on the side of the release layer away from the carrier copper foil, the release layer contains a copper-containing organic compound, and the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu-N bond)". Due to this, the releasability between the carrier copper foil and the ultra-thin copper layer in the ultra-thin copper foil with a carrier is excellent, and this solves the problem that in the conventional technology, the release layer is not uniform in thickness and content, making it difficult to control the peel force.
[0111] The above disclosure is merely a preferred embodiment of the present invention, and the scope of the claims of the present invention is not limited thereto. Therefore, all equivalent technical modifications made by utilizing the specification and drawings of the present invention are included in the scope of the claims of the present invention. [Explanation of symbols]
[0112] E...Ultra-thin copper foil with carrier (also called copper foil laminate structure) 1...Carrier copper foil 2...Release layer 3...Ultra-thin copper layer PP...Dielectric layer material H...Hot press work L...Electrolytic plating solution T...Storage tank R...Guide roller E...electrode
Claims
1. Providing a carrier copper foil; forming a release layer containing a copper-containing organic compound on one side of the carrier copper foil, the chemical structure of the copper-containing organic compound having at least a copper-nitrogen bond (Cu-N bond); forming an ultra-thin copper foil on the surface of the release layer away from the carrier copper foil; The method for producing an ultra-thin copper foil with a carrier, wherein the carrier copper foil is peelable from the ultra-thin copper layer via the release layer.
2. According to Fourier transform infrared spectroscopy (FTIR), the release layer has a wavelength of 1020 cm -1 ~1025cm -1 Position and 1098cm -1 ~1103cm -1 The method for producing an ultra-thin copper foil with a carrier according to claim 1, wherein the carrier exhibits an infrared characteristic absorption peak at each of the positions.
3. The method for producing an ultra-thin copper foil with a carrier according to claim 1, wherein the copper-containing organic compound for forming the release layer is an organic copper complex.
4. The release layer is formed on the carrier copper foil by electrolytic plating using an electrolytic plating solution, the electrolytic plating solution including (1) a nitrogen-containing heterocyclic compound, (2) a copper-containing metal salt, and (3) a buffer; In the electrolytic plating solution, the concentration of the nitrogen-containing heterocyclic compound is 0.05 g / L to 40 g / L, the concentration of the copper-containing metal salt is 5 g / L to 100 g / L, and the concentration of the buffer is 10 g / L to 600 g / L. The method for producing an ultrathin copper foil with a carrier according to claim 1.
5. The method for producing an ultrathin copper foil with a carrier according to claim 4, wherein in the electrolytic plating solution, the nitrogen-containing heterocyclic compound: the copper-containing metal salt: the buffer (mass ratio) is 1:5 to 40:100 to 600.
6. The nitrogen-containing heterocyclic compound is a bicyclic nitrogen-containing heterocyclic compound, the copper-containing metal salt is at least one selected from the group consisting of copper pyrophosphate, copper sulfate, copper carbonate, copper acetate, copper nitrate, copper oxide, copper (I) cyanide, sodium copper cyanide, and potassium copper cyanide, and the buffer is at least one selected from the group consisting of potassium pyrophosphate, boric acid, sulfuric acid, ammonium sulfate, citric acid, ammonium citrate, sodium citrate, sodium acetate, sodium carbonate, potassium tartrate, and sodium gluconate. The method for producing an ultrathin copper foil with a carrier according to claim 4.
7. The carrier copper foil is electroplated in the electrolytic plating solution for a predetermined time, the predetermined time is 1 to 20 seconds, the current density of the electrolytic plating condition is 0.1 to 5 ASD, and the temperature of the electrolytic plating solution is 30 to 60° C. The method for producing an ultra-thin copper foil with a carrier according to claim 4.
8. The chemical structure of the copper-containing organic compound further includes a carbon-hydrogen bond (CH bond, C-H bond), a carbon-nitrogen bond (CN bond, C-N bond), and a nitrogen-hydrogen bond (NH bond, N-H bond). The method for producing an ultra-thin copper foil with a carrier according to claim 1.
9. The method for producing an ultrathin copper foil with a carrier according to claim 1, wherein the nitrogen content of the release layer measured by an X-ray photoelectron spectroscopy (XPS) is 0.1 to 25 mass%.
10. The element ratios of the release layer analyzed by the X-ray photoelectron spectroscopy device are N1s peak area of 15 to 25 atomic%, O1s peak area of 25 to 35 atomic%, C1s peak area of 30 to 40 atomic%, and Cu2p peak area of 5 to 18 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.3 to 0.
9. The method for producing an ultrathin copper foil with a carrier according to claim 9.
11. A carrier copper foil; A release layer formed on one surface of the carrier copper foil; and an ultra-thin copper foil formed on the surface of the release layer away from the carrier copper foil; The release layer includes a copper-containing organic compound, and the chemical structure of the copper-containing organic compound has at least a copper-nitrogen bond (Cu—N bond); The carrier copper foil is capable of being peeled from the ultra-thin copper layer via the release layer.
12. According to Fourier transform infrared spectroscopy (FTIR), the release layer has a wavelength of 1020 cm -1 ~1025cm -1 And, 1098 cm -1 ~1103cm -1 12. The ultra-thin copper foil with a carrier according to claim 11, wherein the copper-containing organic compound of the release layer is an organic copper complex, and the copper-containing organic compound of the release layer exhibits an infrared characteristic absorption peak at each of the positions.
13. The carrier copper foil according to claim 11, wherein the thickness of the carrier copper foil is 10 μm to 50 μm, the thickness of the release layer is 20 nm to 300 nm, and the thickness of the ultra-thin copper layer is 1 μm to 5 μm.
14. The release layer is formed by electrolytic plating of the carrier copper foil with an electrolytic plating solution, the electrolytic plating solution containing (1) a nitrogen-containing heterocyclic compound, (2) a copper-containing metal salt, and (3) a buffer. The ultra-thin copper foil with a carrier according to claim 11.
15. The ultra-thin copper foil with a carrier according to claim 11, wherein the surface roughness of the ultra-thin copper layer on a surface away from the release layer is greater than the surface roughness of the ultra-thin copper layer on a surface in contact with the release layer.
16. The carrier-attached ultrathin copper foil according to claim 11, wherein the peel strength when the carrier copper foil is peeled from the ultrathin copper layer via the release layer is 1 to 20 gf / cm based on JIS Z 0237-2009.
17. According to Fourier transform infrared spectroscopy (FTIR), the release layer exhibits characteristic absorption peaks of carbon-hydrogen bonds (CH bonds, C-H bonds), carbon-nitrogen bonds (CN bonds, C-N bonds), and nitrogen-hydrogen bonds (NH bonds, N-H bonds). The ultra-thin copper foil with a carrier according to claim 11.
18. The nitrogen content of the release layer measured by an X-ray photoelectron spectroscopy (XPS) is 0.1% by mass to 25% by mass, and the element ratios analyzed by the X-ray photoelectron spectroscopy of the release layer are: N1s peak area is 15 to 25 atomic%, O1s peak area is 25 to 35 atomic%, C1s peak area is 30 to 40 atomic%, and Cu2p peak area is 5 to 18 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.3 to 0.
9. The ultra-thin copper foil with a carrier according to claim 11.
19. 19. The ultra-thin copper foil with a carrier according to claim 18, wherein the N1s peak area accounts for 20.63 atomic%, the O1s peak area accounts for 29.78 atomic%, the C1s peak area accounts for 36.77 atomic%, and the Cu2p peak area accounts for 12.82 atomic%, and the ratio of the Cu2p peak area to the N1s peak area is 0.6214.
20. The ultra-thin copper foil with a carrier according to claim 17, wherein a curve diagram of a Cu2p peak is present in X-ray photoelectron spectroscopy (XPS) and focused ion beam analysis (FIB) of the release layer.
Citation Information
Patent Citations
Ultra thin copper foil with very low profile copper foil as carrier and manufacturing method therefor
JP2012219368A
Carrier-attached extremely thin copper foil and method of manufacturing the same
JP2018138702A
Ultra thin copper foil having copper foil with very low profile as carrier
KR1020140035552A
Ultrathin copper foil with carrier, and copper laminated board or printed wiring board
WO2010027052A1
Roughened copper foil, copper foil with carrier, copper-clad multi-layer board, and printed wiring board
WO2019188712A1
Cited By
Copper foil composite structure and production method thereof
JP2025162945A
Copper foil composite structure and method of manufacturing the same
JP7770476B2